Financial responsibility of the state: a comparative analysis of the European countries’ approaches in peacetime and wartime - Barikova, A.; Kobko, V.; Nikitin, V.; Kobko, Ye.; Kobko, R. V.; Кобко, Р. В. (Cuestiones Políticas . – 2023. – Vol. 41, № 77. – P. 422-436, 2023)
Розкрито сутність фінансової відповідальності держави в рамках порівняльного аналізу підходів європейських країн у мирний і воєнний час. Досліджено практику реалізації відповідальності держави в деяких європейських та азіатських країнах і зроблено висновок, що вона склалася саме в мирний час. Однак стверджується, що такий досвід державних фінансів також може бути корисним в українських реаліях реконструкції та відновлення. Проаналізовано українські нормативно-правові акти щодо фінансової відповідальності держави та досліджено відповідні судові рішення. Наголошено, що під фінансовою відповідальністю суб’єктів публічної адміністрації та їх посадових чи службових осіб слід розуміти відшкодування збитків за неправомірні дії у вигляді рішень чи дій, які призвели до порушення чи нехтування права та законні інтереси платників.

The aim of the article was to unveil the essence of the financial responsibility of the State within a comparative analysis of the approaches of European countries, in times of peace and war. The complexity of the subject led to the complex application of research methods, in particular: dialectical, systemic, comparative, synergistic, normative and logical analysis, synthesis. The practice of the implementation of State responsibility in some European and Asian countries was studied and it was concluded that it had been established particularly in times of peace. However, it is argued that such experience of public finance could also be useful in the Ukrainian realities of reconstruction and recovery. Ukrainian legal instruments concerning the financial responsibility of the state were also examined and the respective court decisions were researched. Among other things, it is concluded that, the financial liability of the subjects of public administration and their officials or employees is to be understood in terms of compensation of damages for wrongful acts in the form of decisions or actions that led to infringement or disregard of the rights and legitimate interests of the payers.

Раскрыта сущность финансовой ответственности государства в рамках сравнительного анализа подходов европейских стран в мирное и военное время. Исследована практика реализации ответственности государства в некоторых европейских и азиатских странах и сделан вывод, что она сложилась именно в мирное время. Подчеркнуто, что под финансовой ответственностью субъектов публичной администрации и их должностных следует понимать возмещение ущерба за неправомерные действия в виде решений или действий, которые привели к нарушению или пренебрежению права и законных интересов плательщиков.
Keywords: фінансова політика; інтеграція правового порядку; глобалізація; військовий стан; державне управління; фінансова відповідальність; financial policy; legal order integration; socio-technological globalization; martial law; public administration; financial responsibility; финансовая политика; интеграция правопорядка; глобализация; военное положение; государственное управление; финансовая ответственность